Photodynamic Therapy Is Effective Against Candida auris Biofilms - Bapat, Priyanka S.; Nobile, Clarissa J. (Frontiers in Cellular and Infection Microbiology, 2021)
Fungal infections are increasing in prevalence worldwide. The paucity of available antifungal drug classes, combined with the increased occurrence of multidrug resistance in fungi, has led to new clinical challenges in the treatment of fungal infections. Candida auris is a recently emerged multidrug resistant human fungal pathogen that has become a worldwide public health threat. C. auris clinical isolates are often resistant to one or more antifungal drug classes, and thus, there is a high unmet medical need for the development of new therapeutic strategies effective against C. auris. Additionally, C. auris possesses several virulence traits, including the ability to form biofilms, further contributing to its drug resistance, and complicating the treatment of C. auris infections. Here we assessed red, green, and blue visible lights alone and in combination with photosensitizing compounds for their efficacies against C. auris biofilms. We found that (1) blue light inhibited and disrupted C. auris biofilms on its own and that the addition of photosensitizing compounds improved its antibiofilm potential; (2) red light inhibited and disrupted C. auris biofilms, but only in combination with photosensitizing compounds; and (3) green light inhibited C. auris biofilms in combination with photosensitizing compounds, but had no effects on disrupting C. auris biofilms. Taken together, these results suggest that photodynamic therapy could be an effective non-drug therapeutic strategy against multidrug resistant C. auris biofilm infections.